Framework Development for Detection of Skin Diseases Using Advanced Deep Learning Models and Suggestion of Pharmaceutical Remedy Products - Pal, Subhabaha (Indian Journal of Computer Science, 2022)
Skin diseases are quite common in the present times and majority of the world population is facing these in some form or the other. However, inherent social stigma, attached to skin-related issues specially in the third world countries restricts people from seeking appropriate help from dermatologists unless the issues goes out of proportion. Several researches have been conducted on detection of skin related issues using Artificial Intelligence, however, no proper framework has been developed on how the use of these advanced technologies can directly help the affected individuals. The current work uses advanced models like CNN and Inception V3 models which perform better in terms of detecting cases of skin ailments from images and also suggest a framework through which proper information can be presented to the affected individuals and support them to take proper remedy by automatically suggesting one. This work is an effort to conglomerate the power of deep learning in the detection of skin related issues with the application of proper pharmaceutical products in the form of remedies for skin disease. This work unravels the path for practical application of deep learning algorithms for proper use of pharmaceutical products for benefits of patients.